EFFECT OF YISHENJIANPI RECIPE ON SEMEN QUALITY AND SPERM MITOCHONDRIA IN MICE WITH OLIGOASTHENOZOOSPERMIA INDUCED BY TRIPTERYGIUM GLYCOSIDES - Sheng, Wen; Zhang, Yao-Sheng; Li, Yue-Qing; Wu, Xiao-Ni; Chai, Li-Min; Yue, Li-Feng; Liu, Juan; Ding, Jin; Li, Xian-Rui; Chen, Meng; Shang, Jian-Wei (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background:Kidney tonifying - spleen strengthening method being one of the modalities for treatment of astheno-oligozoospermia is currently commonly used in the clinical setting. To investigate the mechanism of YiShenJianPi (YSJP) Recipe, used in Traditional Chinese Medicine to benefit “the kidney” and strengthen “the spleen”. Materials and Methods: Oligoasthenozoospermia, male BALB/c mice were randomly divided into normal control, disease model, positive control, low-dosage and high-dosage groups. Oligoasthenozoospermia was induced by tripterygium glucosides intragastric administration before treatment started.Through using computer-aided sperm analysis to test the changes in sperm quality, utilizing flow cytometry to test the percentage of sperm with normal mitochondrial transmembrane potential (JC-1 + %), utilizing X-ray microscopy to observe epididymal sperm ultra-microstructure placing special emphasis and photographing the differences in mitochondria of the flagellum region. Results: Compared with DM, sperm quality of the treated mice was significantly better (P<0.05, respectively). Compared with PC, the LD group had significantly better quality sperms, while the parameters in the HD group were numerically better. Compared with NC, all other groups had significantly lower percentage of sperms with normal mitochondrial membrane potential. In PC, LD and HD groups, the percentage of sperms with normal mitochondrial membrane potential was significantly higher than that of D. The 9+9+2 mitochondrial sheath structure was complete in NC but damaged in DM. In the treatment groups, this structure was fairly clear. Conclusion: YSJP improved semen quality with oligoasthenozoospermia by improving sperm mitochondrial membrane potential and restoring sperm mitochondrial ultrastructure.